2005
DOI: 10.1086/427201
|View full text |Cite
|
Sign up to set email alerts
|

Plant Responses to an Edaphic Gradient across an Active Sand Dune/Desert Boundary in the Great Basin Desert

Abstract: In arid ecosystems, variation in precipitation causes broad-scale spatial heterogeneity in soil moisture, but differences in soil texture, development, and plant cover can also create substantial local soil moisture heterogeneity. The boundary between inland desert sand dunes and adjacent desert habitats exhibits abrupt changes in soil and vegetation characteristics that may be associated with differences in plant-available water and nutrients. We hypothesized that differences in plant water status between hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 62 publications
4
49
0
Order By: Relevance
“…herbs) and increasing the dominance index of the community (Koerselman and Meuleman, 1996). Among different environmental factors, changes in water availability associated with soil properties are considered to be the most important selective forces, which shape ecosystem stability in hyperarid zones (Rosenthal et al, 2005;Ravi et al, 2010;Feng, 2015). Our study showed that spatial heterogeneity of soil properties was the major driving force for the spatial distribution of vegetation, with SWC1, SWC3 and BD contributing 59.46 % of the total explanation of vegetation variance ( Table 2).…”
Section: The Spatial Distribution In Heihe Desert Riparian Forest Andmentioning
confidence: 67%
“…herbs) and increasing the dominance index of the community (Koerselman and Meuleman, 1996). Among different environmental factors, changes in water availability associated with soil properties are considered to be the most important selective forces, which shape ecosystem stability in hyperarid zones (Rosenthal et al, 2005;Ravi et al, 2010;Feng, 2015). Our study showed that spatial heterogeneity of soil properties was the major driving force for the spatial distribution of vegetation, with SWC1, SWC3 and BD contributing 59.46 % of the total explanation of vegetation variance ( Table 2).…”
Section: The Spatial Distribution In Heihe Desert Riparian Forest Andmentioning
confidence: 67%
“…Helianthus anomalus and H. deserticola are desert annual sunXowers of hybrid origin from the same ancestral parental cross (Schwarzbach and , Gross et al 2003) that diVer in phenology and are endemic to habitats diVering in water and nutrient availability (Rosenthal et al 2005a;Ludwig et al 2006). We asked the following questions: (1) is there direct and indirect selection on integrated leaf WUE, N, area and succulence and (2) is direct selection on WUE consistent with hypothesized drought/dehydration escape and avoidance strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Early authors (Stebbins 1957;Grant 1958;Templeton 1980) (McCarthy et al 1995;Buerkle et al 2000). Karyotypic divergence and spatial isolation are well documented in natural hybrid species (Gallez and Gottlieb 1982;Rieseberg 1991;Rieseberg et al 1995;Hirai et al 2000), and most hybrid species occupy habitats that are different or extreme compared with the parental species (Abbott 1992; Arnold 1997;Rieseberg 1997;Schwarzbach et al 2001;Rosenthal et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, three natural hybrid sunflower species, Helianthus anomalus, Helianthus deserticola, and Helianthus paradoxus have distinct multitrait phenotypes and occupy very different habitats (Heiser et al 1969;Rosenthal et al 2002Rosenthal et al , 2005Welch and Rieseberg 2002a). Many of the traits that distinguish these species are extreme relative to parental values, and phenotypic selection experiments indicate that some are favored in their native habitats (Lexer et al 2003b;Gross et al 2004;Ludwig et al 2004).…”
mentioning
confidence: 99%